The Revolving Door of Sell-Side Analysts - Lourie, Ben (The Accounting Review, 2019)
ABSTRACT Equity analysts are often hired by firms they cover. I document the extent to which this revolving door phenomenon impairs analysts' independence. I do this by examining the presence of biased research reports issued during the year before analysts are employed by a firm they cover. I find that during their final year, revolving door analysts bias their EPS forecasts, their target prices, and their recommendations in a direction that suggests that they are attempting to gain favor from their prospective employers. Specifically, relative to other analysts, revolving door analysts issue more optimistic reports on the firms that hire them, and they issue more pessimistic reports on firms that do not hire them. These results suggest the presence of strategic bias, although more innocuous interpretations cannot be completely ruled out. JEL Classifications: G14; G17; G24; G28; M41. Data Availability: Data are available from public sources identified in the text.